The Effect of Financial Performance on Share Price for the 2017-2021 Period (Case Study of Food and Beverage Sub-Sectors Listed on the IDX) - Hastuti, Rini; Rumiasih, N. A; A Syukur, Dudung (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
In this study the authors have a goal to see whether there is an effect of financial performance on stock prices. The financial performance ratios used in this study are the current ratio, debt to equity, return on equity and Total asseits turnoveir. This study uses quantitative data. The sampling method is using purposive sampling method. The hypothesis testing method in this study uses multiple linear regression analysis, correlation coefficient, determination coefficient, partial test (T test) and simultaneous test (F test). The independent variables in this study are the ratio of liquidity, solvency, profitability and activity and the dependent variable in this study is stock prices. The results of this study simultaneously liquidity, solvency, profitability and activity have an effect on stock prices, while partially liquidity, solvency and profitability have a significant negative effect on stock prices and activity has a significant positive effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the period 2017 – 2021